2009
DOI: 10.1590/s0004-282x2009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to depressive symptoms among elderly people with chronic vestibular dysfunction

Abstract: -Objective: To identify factors relating to depressive symptoms among elderly people with chronic vestibular dysfunction. Method: This was a cross-sectional study in which 120 elderly people with chronic vestibular dysfunction answered the Geriatric Depression Scale questionnaire. Multivariate linear regression analysis was performed (p<0.05 and 95% CI). Results: The patients presented a mean score of 12.86±6.39 points on the Geriatric Depression Scale, and 67 of them (55.8%) scored above the cutoff of 11 poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 21 publications
3
33
0
4
Order By: Relevance
“…A study that assessed elderly patients with vestibular diseases found that turning the head and keeping the head in a specific position were the most common movements or positions associated with dizziness 20 . The complaint of dizziness was more common in females compared to males (50.6% vs. 35.2%), which is supported by several studies 4,9,10,13,20,21,46,48 . Some studies suggest a correlation between age and dizziness, with a higher prevalence in older age groups 4,9 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A study that assessed elderly patients with vestibular diseases found that turning the head and keeping the head in a specific position were the most common movements or positions associated with dizziness 20 . The complaint of dizziness was more common in females compared to males (50.6% vs. 35.2%), which is supported by several studies 4,9,10,13,20,21,46,48 . Some studies suggest a correlation between age and dizziness, with a higher prevalence in older age groups 4,9 .…”
Section: Discussionsupporting
confidence: 68%
“…Although these factors were independently associated with dizziness in the present study, our statistical analysis did not provide any estimate of the weight of these associations. A study of 120 elderly individuals with chronic vestibular syndrome suggested -in a linear regression model -that having more symptoms of depressions was associated with memory and concentration disorders, among other factors 21 . Poor perception of health was independently associated with dizziness, which concurs with other population-based studies 4,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 28 patients who underwent treatment, 17 (61%) were treated with the repositioning maneuver, problems such as depression 4 . According to a study 19 , emotional changes are due to the impact of the perceived impairments on these patients' mindset, which interferes with their activities of daily living, social life, and self-image.…”
Section: Resultsmentioning
confidence: 99%
“…Shirley Nogueira Soares (1) , Maria Adriana da Silva Gonçalves (2) , Claudiana Gomes Teixeira (3) , Priscila Caetano Romualdo (4) , Juliana Nunes Santos (5) (1) Faculdade de Estudos Administrativos -FEAD, Belo Horizonte, MG, Brazil. (2) Faculdade de Estudos Administrativos -FEAD, Belo Horizonte, MG, Brazil.…”
Section: Influência Da Reabilitação Vestibular Na Qualidade De Vida Dunclassified
See 1 more Smart Citation